A Review of Cost Reduction Strategies – With Special Reference to Food and Beverage Industry in Uttarakhand - Deepak Sahni, Anisha Khanduja (Mathematical Statistician and Engineering Applications, 2023)
It is a known fact that hospitality industry can contribute a lot for the growth and progress of any country or a state. An extraordinary increase in the diversity, demand for, as well as the quality of product and service categories has occurred as the sector has grown. These factors have led to a strong competition in which customers are tougher to target and costs are challenging to control. There is a constant flux of factors affecting the food and beverage supply chain in the modern era and many companies are shifting their attention to processes like cost reduction, supplier relationship management and contract management in order to minimize the impact of these factors on their profitability. Cost-cutting strategies are examined in this article, as well as the company’s own internal operations including the costs of retaining highly-trained personnel, locating the correct high quality but cost-effective suppliers, and keeping track of every purchase. In an industry that is susceptible to high waste, spoilage, and inventory issues, there is a pressing need for corporations to acquire, obtain, and stock with the utmost care. There has been a lot of anger and even the demise of certain businesses in the F&B sector recently because of how much trash is generated. Restaurants everywhere are scrambling to find ways to keep diners happy and minimize loss via attrition. Starting cost-cutting initiatives has become an essential aspect of F&B strategy since it has improved performance, reduced waste, and increased overall customer satisfaction by reducing wasteful expenditure and boosting savings.